Molecular analysis of six Rhynchospio Hartman, 1936 species (Annelida: Spionidae) with comments on the evolution of brooding within the group - Radashevsky, Vasily I.; Malyar, Vasily V.; Pankova, Victoria V.; Nuzhdin, Sergey V. (Zootaxa, 2016)
Rhynchospio Hartman, 1936 is a small group of spionid polychaetes currently comprising ten described species distributed mainly in the Pacific. Five species examined to date are hermaphrodites producing spermatozoa with long nuclei, oocytes with thin and smooth envelopes, and dorsally brooding their offspring. Since our first molecular analysis of four Rhynchospio species, we have collected additional material from Northern Territory, Australia, and Oregon, USA. Herein, we describe the gamete and adult morphology of the newly collected material and use molecular analyses to provide new insight on the phylogenetic relationships of six Rhynchospio species. Adults of R. cf. foliosa from Oregon are hermaphrodites, but in contrast to other Rhynchospio, they produce spermatozoa with short nuclei (ect-aquasperm), oocytes with thick vesiculate envelopes, and likely have a holopelagic larval development. Analysis of four gene fragments, comprising mitochondrial 16S rDNA, and nuclear 18S, 28S rDNA, and Histone 3 (2516 bp in total) showed Rhynchospio to be a monophyletic group, with R. cf. foliosa being a distant sister to the five other species. Rhynchospio cf. foliosa was closer to M. arctia having ect-aquasperm and vesiculate thick-envelop oocytes (p = 14.40%) than to Spioninae members B. proboscidea and P. elegans, having introsperm and oocytes with thin and smooth envelopes (p = 15.39 and 16.54%, respectively). We hypothesize that brooding might have evolved from free-spawning inside the Rhynchospio clade, but this hypothesis should be tested in a future analysis.